Development of a digital flipbook as instructional media for pencak silat kicking movements - Ni Putu Asti Anggita Cahyani; Ni Luh Putu Spyanawati; I Gede Suwiwa (Universitas Sriwijaya, 2025)
Research Problems: The teaching materials used are still not very varied, only sourced from lecturers' and students' books, and there has been no development of teaching materials that help students learn independently. Research Objectives: This study aims to develop digital-based pencak silat teaching materials (flipbook) in the Theory and Practice course Methods: In this study, development was used with the ADDIE model, which consists of 5 stages, namely, analysis, design, development, implementation, and evaluation. The research design includes expert validity tests, product trials, and practicality tests, involving research subjects from the lecturers and students of Physical Education, Health, and Recreation at the Faculty of Sports and Health, Ganesha University of Education. Data were collected through questionnaires and analysed descriptively, qualitatively and quantitatively. Results: The research findings show that all expert validity tests (content/material 97%, instructional design 96.2%, learning media 93.7%, and field practitioner 95%) received a very good qualification, indicating a very high level of validation for the developed product or material. Meanwhile, the field trials indicated that the product was rated good in the individual trial (89.8%) and small group trial (87.3%), and very good in the large group trial (91.5%), demonstrating a high and acceptable level of practicality by users. Conclusion: It can be concluded that digital-based pencak silat teaching materials (flipbooks) are used in the course. Pencak Silat learning of kicking material is very suitable for use by students of the Faculty of Sports and Health.